Molecular Design Rule of Phthalocyanine Dyes for Highly Efficient Near‐IR Performance in Dye‐Sensitized Solar Cells. Issue 23 (9th April 2013) - Kimura, Mutsumi; Nomoto, Hirotaka; Suzuki, Hiroyuki; Ikeuchi, Takuro; Matsuzaki, Hiroyuki; Murakami, Takuro N.; Furube, Akihiko; Masaki, Naruhiko; Griffith, Matthew J.; Mori, Shogo
Abstract A series of zinc–phthalocyanine sensitizers (PcS16–18) with different adsorption sites have been designed and synthesized in order to investigate the dependence of adsorption‐site structures on the solar‐cell performances in zinc–phthalocyanine based dye‐sensitized solar cells. The change of adsorption site affected the electron injection efficiency from the photoexcited dye into the nanocrystalline TiO2 semiconductor, as monitored by picosecond time‐resolved fluorescence spectroscopy. The zinc–phthalocyanine sensitizer PcS18, possessing one carboxylic acid directly attached to the ZnPc ring and six 2, 6‐diisopropylphenoxy units, showed a record power conversion efficiency value of 5.9 % when used as a light‐harvesting dye on a TiO2 electrode under one simulated solar condition.